THE ANALYSIS OF STUDENTS’ DIFFICULTIES ON ENGLISH SKILLS AT BINA INSAN UNIVERSITY, LUBUKLINGGAU - Riance , Astri; Herlina, Herlina; Sinta, Sinta; Saftari, Maya (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study is entitled the analysis of students’ difficulties on English Skills at Bina Insan University. This study aims to find the difficulties faced by Bina Insan University students in learning English. The method used in this study is descriptive research, with a population of 178 Management students, and the sampling technique used in this study uses random sampling, with 71 students as samples. From several questionnaires distributed, it was found that many students still find difficulties in mastering 4 skills in English, therefore teachers are expected to be able to increase their creativity in choosing interesting, effective, and efficient learning methods and strategies for students.